FRI0675 AUTOIMMUNE PERIPHERAL ULCERATIVE KERATITIS: ASSOCIATED ETIOLOGY, CLINICAL CHARACTERISTICS, TREATMENT AND VISUAL PROGNOSIS. (June 2019) - Hubbe-Tena, Claudia; Fernandez, Mariana; Davila-Avila, Ned Merari; Cheja, Rashel; León-Oritz, Pablo; Concha, Luz Elena
Abstract : Background: Peripheral ulcerative keratitis (PUK), a rare sight-threatening condition, is an inflammatory corneal disease with an estimated incidence of 8 to 10 cases per million. PUK is characterized by the presence of an epithelial defect with progressive stromal corneal degradation and juxtalimbal thinning. Objectives: To describe the associated etiology, demographic and clinical characteristics, treatment and visual prognosis of patients with PUK and autoimmune disease. Methods: A retrospective, transversal, descriptive, observational cohort study was performed. The clinical file of all patients that had been diagnosed with PUK at the Inflammatory Eye Disease Clinic and who came to a follow-up appointment between January 2014 through February 2018 was evaluated. With a minimum follow-up of 6 months since PUK diagnosis. Quantitative data was calculated in terms of means and standard deviations. Qualitative data in frequencies. Chi-square and rank sum tests were used to compare groups. Kaplan-Meier methods to estimate survival rates according to treatment. Comparisons of survival rates between treatments were performed using log-rank tests. A p level of <0.05 was considered significant. Statistical analyses were performed using SPSS 24.0 Results: A total of 109 patients (155 eyes; 79.8% female; mean age 53.9 ±12.5 (23 to 81) years) were included. The frequency of the association between PUK and an autoimmune systemic disease, was 86.3% (94). The leading etiology was RA (52.3%; n=57); VAA (30.3%; n=33), being GPA the foremost recognized in this group (84.8%; 28/33). Other were SLE, PSS, JIA, and ReA. When PUK started, RA was already diagnosed in 87.7% (50/57); 18.2% (6/33) of AAV. Mean disease evolution in RA was 15 ± 8.2 years; AAV had 3.9 ± 5.6 years (p=0.05). 29% (n=17) of RA untreated; only 4 (12.2%) AAV were immunosuppressed by the time PUK settled. Systemic autoimmune activity, was found in 31.5% (18/57) of RA and 90.9 (30/33) of AAV. Arthralgia was foremost referred by RA (94.4%;17/18); ear–nose–throat symptoms were in AAV (86.6%; 26/30). In the latter, some degree of renal dysfunction was found in 33.3% (10/33). PUK characteristics in RA and AAV. Moderate (34.2%) and mild (36.3%) PUK were more frequently seen in RA; whereas moderate (36.3%) and severe (33.3%) in AAV (p=0.016). RA associated PUK commonly involved the inferior corneal quadrant (54.3%), as AAV the superior one (73.8%; p < 0.01). Corneal perforation was more frequent in RA than AAV (54.5% vs 22.7%; p=0.481); although the risk of perforation associated to RA didn't show statistical significance (OR 1.14 [IC 95% 0.8 - 1.63]). Necrotizing scleritis was more commonly seen in AAV (RA n=1 vs AAV n=10. The more frequent instated treatment in RA was oral prednisone combined with oral DMARDs (31.6%; 18/57). More aggressive therapy (MPS, CYC or Rituximab) was designated in 22.8% (n=13). On the other hand, 78.7% (26/33) of AAV were managed with the MPS-pred scheme merged with CYC (36.4%; n=12) or Methotrexate (42.4%; n=14). Conclusion: RA and AAV are the more frequent autoimmune diseases that can manifest with PUK. In RA, the lack of arthritis could be mistaken as quiescent, and wrongly undertreated, allowing it to progress to a vasculitic stage. It may impact their life quality if complicated with corneal perforation. In AAV the PUK can be the initial sympton of the disease and is associated with a more sever ocular presentation. Routine ophthalmologic examinations might help the rheumatologist to assess RA and AAV activity and treatment. References: [1.] John SL, Morgan K, Tull AB, Holt JL. Eye. 1992;6:630-6. Disclosure of Interests: None declared